In utero exposure to butyl benzyl phthalate induces modifications in the morphology and the gene expression profile of the mammary gland: an experimental study in rats - Russo Irma H; Wang Richard; Santucci-Pereira Julia; Moral Raquel; Lamartiniere Coral A; Russo Jose (BMC, 2011)
Abstract Background Environmental estrogens are exogenous estrogen-mimicking compounds that can interfere with endogenous endocrine systems. Several of these endocrine disruptors have been shown to alter normal development and influence tumorigenesis in experimental models. N-butyl benzyl phthalate (BBP), a widely used plasticizer, is a well-known endocrine disruptor. The aim of this study was to elucidate the effect of prenatal exposure to BBP on the morphology, proliferative index, and genomic signature of the rat mammary gland at different ages. Methods In utero exposure was performed by gavage of pregnant Sprague Dawley CD rats with 120mg or 500mg BBP/kg/day from day 10 post-conception to delivery. Female litters were euthanized at 21, 35, 50 and 100 days. The morphology and proliferative index of the mammary gland were studied from whole mount preparations and BrdU incorporation, respectively. Gene expression profile was assessed by microarrays. Several genes found differentially expressed and related to different functional categories were further validated by real time RT-PCR. Results Prenatal exposure of BBP induced delayed vaginal opening and changes in the post-natal mammary gland long after the end of the treatment, mainly by 35 days of age. Exposure to the high dose resulted in modifications in architecture and proliferative index of the mammary gland, mostly affecting the undifferentiated terminal end buds. Moreover, the expression profiles of this gland in the exposed rats were modified in a dose-dependent fashion. Analysis of functional categories showed that modified genes were related to immune function, cell signaling, proliferation and differentiation, or metabolism. Conclusions Our data suggest that in utero exposure to BBP induced a delayed pubertal onset and modified morphology of the mammary gland. These alterations were accompanied by modifications in gene expression previously associated with an increased susceptibility to carcinogenesis.